Estratégia e legitimidade em organizações sociais: o Serviço Social do Comércio (SESC) - Espírito Santo, Marcela do (2014)
The dilemmas and strategic challenges for economic viability and legitimacy faced by social organizations in Brazil -organizations without economic purpose -resemble those faced by other types of organization in different parts of the world. The dominant literature of management and strategy favors, in its framework, concepts and practices that support and are supported by large private corporations. The growing influence of these organizations in academia and society helps explain the role of importance that strategies of corporate social responsibility have achieved in the legitimation of neoliberal ideology and practices which help to reaffirm. In turn, this framework helps to explain the marginal position that social organizations occupy inside the area of strategic management. This dissertation seeks to expand the discussion of the studies in the field of strategic management that addressed the hegemonic construction of the field, their processes of legitimation and diffusion and their critical approaches, including the aspect of coloniality in which the dominant literature falls. The understanding of strategic trajectory of a social organization, the Social Service of Commerce - SESC, was given by the research processes of legitimation mobilised within the organization itself and in the context in which it operates. For such, the contextualist perspective allowed the observation by internal and external relationships established and the changes and continuities promoted due to its legitimacy. To represent organizations as political and cultural systems that influence and are influenced by the environment, this research promotes understanding of the ideological components and power in strategic management, commonly naturalized by the mainstream literature, making room for even the decolonization of the area of strategic management, emphasizing the diversity of organizations and practices, and the possibility of coexistence of different types of organizations in the area.